Rationale and design of Low-Frequency REpetitive TRanscranial Magnetic Stimulation Combined with Endovascular Treatment in ACute Ischaemic StrokE (RETRACE II): a randomised double-blind controlled multicentre phase II pilot study - Yongjun Wang; Zixiao Li; Hao Wang; Wenhuo Chen; Xinsheng Han; Wenjie Wang; Lingling Ding; Tingyu Yi; Gaocai Zhang (Stroke and Vascular Neurology)
Background While endovascular therapy (EVT) remains the primary treatment for acute ischaemic stroke (AIS) management, persistent functional deficits in patients with successful recanalisation underscore the necessity for complementary neuroprotective strategies.Aim To investigate the safety and efficacy of low-frequency repetitive transcranial magnetic stimulation (LF-rTMS) as a potential adjunctive neuroprotective intervention following EVT in AIS patients.Design The Low-Frequency REpetitive TRanscranial Magnetic Stimulation Combined with Endovascular Treatment in ACute Ischaemic StrokE (RETRACE-II) trial is a phase II, multicentre, prospective, randomised, double-blind, sham-controlled pilot study. 60 successfully recanalised AIS patients with anterior circulation occlusion were equally randomised (1:1) to active LF-rTMS or sham intervention. The intervention involved administration of 1200-pulse 1-Hz LF-rTMS sessions (two times per day for 3 consecutive days) targeting the ipsilesional primary motor cortex (M1), initiated within 24 hours of symptom onset. Sham procedures maintained equivalent positioning with deactivated magnetic output. Standardised protocol assessments were conducted at 3-day (postintervention), 7-day and 90-day follow-ups.Study outcomes The primary efficacy endpoint was the proportion of early neurological recovery (defined as a reduction of ≥4 points on the National Institutes of Health Stroke Scale (NIHSS) or achieving a score of 0–1) at 3 days. Secondary outcomes included ischaemic penumbral salvage volume ratio, final infarct volume measured by brain MRI at 7 days, and modified Rankin Scale score at 90 days. Safety outcomes encompassed symptomatic intracranial haemorrhage, neurological deterioration (≥4-point increase in NIHSS score) and all-cause mortality through 90-day follow-up.Discussion RETRACE-II establishes methodological rigour for evaluating neuromodulation therapies during the hyperacute stroke phase, with findings expected to inform future trials and advance combination therapy paradigms in cerebrovascular neuroprotection.Trial registration number NCT06064747.